Faktor-Faktor Determinasi Purchasing Decision Laptop Merek Apple (Studi Pada Pengunjung Paragon Mall Semarang) - Dwi Noor Rohman; Hendri Hermawan Adinugraha (Dinamis : Journal of Islamic Management and Bussiness, 2021)
There are many brands of laptop, such as Acer, Toshiba, HP, Apple, Dell, Asus and Lenovo, etc which each has advantage and disadvantage also has its own enthusiasts. Based on market share in 2014-2016, all brands are fluctuating, but Apple, during the period 2014-2016 continues to decline from 7.4% in 2014 to 5.2% in 2015 even lower and lower it's 3.3% in 2016. That shows the consumers awarenes on Apple is also low. Many factors can influence on purchasing decisions of Apple Laptops, such as product quality, brand awareness, brand image and trust. The purpose of this study is to analyze the impact of product quality, brand awareness, brand image and trust toward purchasing decision of Apple Brand Laptops in Semarang. The population in this study were consumers who purchased Apple's brand laptop in Semarang city by 100 respondents as sample. The type of data used the primary data.  Sampling techique used non-random type of purposive sampling. The data method collection using questionnaires and analysis techniques used multiple regression. The result shows that product quality, brand awareness, brand image, consumer trust has a positive and significant influence simultantly on purchasing decisions.